2023
DOI: 10.1177/00472875231158588
|View full text |Cite
|
Sign up to set email alerts
|

How do Different Types of User-Generated Content Attract Travelers? Taking Story and Review on Airbnb as the Example

Abstract: User-generated content (UGC) has been validated as an important factor in travel decisions. However, it is still unclear whether different types of UGC function differently. Social cognitive theory was applied to investigate the different effects of two types of UGC, Story and Review on Airbnb, on attracting travelers through 2,271 accommodations in Beijing from December 2018 to September 2019 via the spatial Durbin model. The results indicate that, first, Story plays a positive direct role on reservation, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Suess et al (2021) also found that consumers with prior experiences had higher emotional solidarity, positive emotions, community well-being, and personal quality of life than those without prior experiences. More recently, Li et al (2023) showed that stories can attract newcoming travelers, and reviews can attract extant travelers. These studies highlight important differences between purchase intention and repurchase intention.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Suess et al (2021) also found that consumers with prior experiences had higher emotional solidarity, positive emotions, community well-being, and personal quality of life than those without prior experiences. More recently, Li et al (2023) showed that stories can attract newcoming travelers, and reviews can attract extant travelers. These studies highlight important differences between purchase intention and repurchase intention.…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Additionally, Airbnb's Superhost program has been found to positively affect host prices. According to a study by Chen and Xie (2017) [80] and Li, Li, Liu and Fan (2023) [81], Airbnb Superhosts commanded higher prices than non-Superhosts. This can be attributed to the fact that Superhosts are recognized by Airbnb for their high level of hospitality and service, which in turn increases their credibility and trustworthiness among potential guests.…”
Section: Hypothesis Formulationmentioning
confidence: 99%